2020
DOI: 10.3390/app10114013
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications in Epitaxial Graphene on SiC Following 10 keV Nitrogen Ion Implantation

Abstract: Modification of epitaxial graphene on silicon carbide (EG/SiC) was explored by ion implantation using 10 keV nitrogen ions. Fragments of monolayer graphene along with nanostructures were observed following nitrogen ion implantation. At the initial fluence, sp3 defects appeared in EG; higher fluences resulted in vacancy defects as well as in an increased defect density. The increased fluence created a decrease in the intensity of the prominent peak of SiC as well as of the overall relative Raman intensity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Notably, the above-listed examples of sensing applications concern only unmodified pristine epitaxial graphene. At the same time, there is a great deal of interest in epitaxial graphene sensitivity improvement by chemical functionalization [28,29], defect engineering [30,31], and metal oxide nanoparticle decoration [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the above-listed examples of sensing applications concern only unmodified pristine epitaxial graphene. At the same time, there is a great deal of interest in epitaxial graphene sensitivity improvement by chemical functionalization [28,29], defect engineering [30,31], and metal oxide nanoparticle decoration [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the unintentional doping of epitaxial graphene by environmental gases and other molecules, the electronic properties of epitaxial graphene on SiC can be modulated by the intentional incorporation of external dopants, as was demonstrated in another study [3]. Nitrogen ion implantation was proposed as an instrumental approach to stabilize the n-type conductivity in epitaxial graphene without serious structural damage.…”
Section: Critical Aspects Of Epitaxial Graphene Growth: Recipes Prope...mentioning
confidence: 94%
“…Two research works touch on crucial aspects of early stage of graphene growth, namely buffer layer formation [1], and graphene quality estimation [2]. Kaushik et al [3] reported on a principal possibility to tune structural and electronic properties of epitaxial graphene through nitrogen ion implantation. Fundamental knowledge on both copper electrodeposition and atomic layer deposition of high-k insulators on epitaxial graphene/SiC is provided by the authors of [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has also been proposed in the literature that the epitaxial graphene structure and electronic properties could be tuned by nitrogen ion injection. [64] The graphene obtained by the SiC epitaxial method was very clean and free of contamination or defects from transfer, and could be directly applied to device preparation. However, due to the expensive price of the SiC substrate and the high temperature required for epitaxial preparation, the cost of graphene prepared by SiC epitaxy was expensive.…”
Section: Sic Epitaxial Methodsmentioning
confidence: 99%